Correlation of apoptosis with tumour cell differentiation, progression, and HPV infection in cervical carcinoma. Issue 2 (February 1996) - Shoji, Y; Saegusa, M; Takano, Y; Ohbu, M; Okayasu, I
Abstract : AIMS: To clarify the significance of apoptosis in the progression of uterine cervical neoplasias, including cervical intraepithelial neoplasia (CIN), microinvasive carcinoma (MIC), and invasive squamous cell carcinoma (ISCC) categories, in relation to cell proliferation and human papilloma virus (HPV) infection. METHODS: Forty six cases of CIN I/II, 75 of CIN III, 16 of MIC, and 44 of ISCC were examined using formalin fixed and paraffin wax embedded samples. The TdT mediated dUTP-biotin nick end labelling (TUNEL) method for detection of apoptotic cells was performed along with Ki-67 immunohistochemistry. Presence of HPV-DNA was confirmed by PCR-RFLP assay. RESULTS: Apoptotic labelling indices, calculated after counting positive nuclei among at least 2000 nuclei, showed significant positive correlation with histological malignant grading in CIN and tumour cell invasion into stroma. In contrast, similar Ki-67 labelling index values were found in CIN, MIC, and ISCC. Although HPV-DNA was detected in 35/46 CIN I/II (76.1%), 53/74CIN III (71.6%), 9/16 MIC (56.3%), and 36/44 ISCC (81.8%), there was no apparent relation with the apoptotic labelling indices. CONCLUSIONS: Apoptosis in cervical neoplasias may be closely related to tumour cell differentiation and progression. It also seems unlikely that HPV itself is directly related to pathways regulating apoptosis.